Description of the larva and pupa of Limnephilus hamifer Flint 1963 (Trichoptera, Limnephilidae) from Costa Rica - Springer, Monika; Bermúdez-Monge, Jenny (Zootaxa, 2018)
The larva and pupa of Limnephilus hamifer Flint 1963 are described and illustrated for the first time. The description is based on material collected and reared from the Cerro de la Muerte mountain range in Costa Rica, and from additional specimens deposited at the Zoological Museum of the University of Costa Rica. The distribution of this species is restricted to high mountain areas of Costa Rica and Panamá and constitutes the most southern distribution of the genus on the American continent.